ANALYZING THE INFLUENCE OF FARMER FIELD SCHOOL (FFS) ON THE INCOME OF RICE FARMERS USING QUANTILE REGRESSION - Leomarich F. CASINILLO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study looks into the influence of Farmer Field School (FFS) in enhancing rice farmers' income in Babatngon, Leyte, Philippines. The article also aimed to determine the significant factors that affect the rice income in the aspect of the rice production process under the FFS program. Secondary data were considered from the existing current study in the literature that dealt with rice farmers who finished their training in FFS. This study used some standard statistical measures to summarize and describe the data collected and employed quantile regression to capture the significant factors affecting the income of rice farming as influenced by FFS. The results of the survey depicted that the farmers who graduated with FFS training have high knowledge, positive attitude, and very great extent in their practices on what they have learned from crop management and the PalayCheck system. Based on the quantile regression models, the level of income in rice farming is influenced by a lower number of years in farming. This implies that younger farmers are more productive and efficient in enhancing their economic income since they are more competitive than traditional farmers. In addition, the regression models revealed that knowledge and attitude toward FFS do not influence their rice income unless it is implemented and adopted. Moreover, it is depicted that the practices of FFS farmers significantly influenced their level of income at a 10% level. Hence, FFS training has improved the productivity of farmers, and positively impacted their economic income and decision-making process. Furthermore, the study suggested that the FFS program must continually reach out to more small-scale farmers, especially in rural areas to attain sustainability in the country.